Implementasi Teacher Professional Development dengan Penerapan Lesson Study di Sekolah Muhammadiyah - Testiana Deni Wijayatiningsih; Riana Eka Budiastuti; Dodi Mulyadi; Muhimatul Ifadah; Siti Aimah; Yustinah Yustinah (Warta LPM, 2022)
Several teachers in SMP, SMA, and SMK Muhammadiyah in Central Java have not implemented Lesson Study for Teacher Professional Development, especially in SMP Muhammadiyah 1 Cilacap, SMK Muhammadiyah Bumiayu, SMK Muhammadiyah Boja, SMK Muhammadiyah Pekalongan, and SMA Muhammadiyah Wonosobo. The implementation has two objectives, such as to analyze and assess teacher professional development via lesson study in six Muhammadiyah schools. This implementation employed descriptive quantitative and lesson study methodologies to examine the process of implementing lesson study through training models, brainstorming, and group discussions and to measure the improvement of instructors’ viewpoints before and after professional development. The performance results show that teachers actively discussed and collaborated to improve the learning process, from lesson design to open class. The teacher’s perspective questionnaire in their professional development fell into the excellent category, with an average category level above three as the results increased compared to the pre-result before implementation, category level two. All in all, teachers should be more innovative and imaginative to improve their professionalism.